Penguatan Literasi dan Lingkungan Sosial sebagai Upaya Transformasi Paradigma Masyarakat terhadap HIV/AIDS - Muhammad Nur; Syamsir Syamsir; Muhammad Asikin (Celebes Health Journal, 2026)
Public stigma against people living with HIV/AIDS (ODHA) remains a major obstacle in efforts to control the HIV epidemic. Health literacy and the social environment play a role in shaping the public's perception of ODHA. This study aims to analyze the influence of literacy and the social environment on public stigma within a community-based community service framework. The study used a cross-sectional analytical design. The study was conducted in the Salimbongan Community Health Center (Puskesmas) area of ​​Pinrang Regency from October to December 2025. A sample of 200 respondents was selected purposively. Data were collected using a structured questionnaire. Analysis was performed using univariate, bivariate analysis using the Chi-square test, and multivariate analysis using logistic regression. Some respondents still exhibited stigma against ODHA. Bivariate analysis showed a significant relationship between knowledge, perceptions, family attitudes, and community leaders' attitudes with stigma (p<0.05). Multivariate analysis showed that community leaders' and family attitudes were the most dominant determinants of public stigma after controlling for other variables. Strengthening literacy alone is not sufficient to reduce stigma. Community-based interventions involving key social actors are more effective in transforming societal attitudes toward HIV/AIDS.